The Pengaruh Ukuran Perusahaan Dan Profitabilitas Terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Sub Sektor Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Iindonesia (Bei) Periode 2015 – 2021) - Yobi Mulyana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Earnings management is the activity of managers of pharmaceutical companies in an effort to influence financial statement information that aims to deceive stakeholders who want to know the performance and condition of the company. This activity is thought to be influenced by company size and profitability factors. So this study aims to find out, analyze and explain how company size, profitability and earnings management and the effect of profitability measures on earnings management in manufacturing companies sub-sector of Pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2021 either partially or simultaneously. The research method uses a quantitative approach with descriptive and verification analysis. The research sample was 5 pharmaceutical companies out of a total of 11. The unit of analysis used multiple linear regression analysis through classical assumption testing. The results showed that company size and profitability were in good category, while earnings management was quite good. The results of the partial analysis show that firm size has no effect but is positive on earnings management and profitability has a significant positive effect on earnings management. And together that firm size and profitability have a significant positive effect on earnings management. Keywords: company size, profitability, earnings management